Pengaruh Disiplin, Motivasi, Dan Penilaian Kinerja Terhadap Produktivitas Karyawan - Marco Delvico Sihotang (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The aim of this research is to ascertain how, in an oil palm plantation environment, the motivation, discipline and performance appraisal of PT Kedawi Jaya employees influence their output. The company is located in Lapangan Bomban Hamlet, Sennah Village, Pangkatan District, Labuhanbatu Regency, North Sumatra Province. The research population was nineteen workers in the harvest/production section and all of them were used as samples. Questionnaires are the main instrument used in the quantitative data collection technique of this research methodology. Descriptive statistics are used to examine the data collected to characterize the distribution of research data and respondent attributes. Based on the research results, (1) employee productivity is significantly and positively influenced by work discipline (significant value 0.002), (2) work motivation has a significant positive effect (significant value 0.035), (3) performance evaluation increases productivity significantly (significant value 0.039), and (4) these three factors simultaneously have a significant effect on employee productivity (significant value 0.000). To encourage increased productivity in general, it is recommended that PT Kedawi Jaya focus more on improving staff discipline, incentives and performance reviews. Actions that can be taken include using personal protective equipment (PPE), providing training to improve discipline, and creating plans to maintain employee motivation and make the performance appraisal process more transparent.